Polyether Ether Ketone (PEEK) Properties and Its Application Status. Issue 1 (March 2020) - Ling, Xuanzhe; Jing, Xishuang; Zhang, Chengyang; Chen, Siyu
Abstract: The physical, chemical and mechanical properties of polyether ether ketone (PEEK) materials have been comprehensively analyzed. Based on methods for reinforcing modification of PEEK, this review has investigated the application status of PEEK materials, summarized the current production and research and development status quo of PEEK at home and abroad and suggested that the application of PEEK should be promoted.